PENGARUH PEMBERIAN JUS ALPUKAT TERHADAP PENINGKATAN KADAR HEMOGLOBIN PADA IBU HAMIL TRIMESTER III DENGAN ANEMIA - Noviani, Fitri; Triani , Yuyun (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Background: Anemia in third-trimester pregnant women remains a significant health problem with a high prevalence in Indonesia. This condition can lead to serious complications for both the mother and the fetus. Although Fe tablet supplementation has been provided, cases of anemia are still found, indicating the need for alternative interventions. Avocado juice, with its content of iron, vitamin C, and folic acid, has the potential to increase hemoglobin levels. This study aimed to analyze the effect of giving avocado juice on increasing hemoglobin levels in anemic third-trimester pregnant women. Method: This study used a quantitative design with a one group pre-test-post-test design. The sample consisted of 20 anemic third-trimester pregnant women (hemoglobin levels ≤ 11 g/dl) at PMB Eliyana, South Lampung. The intervention was the administration of 200cc of avocado juice per day for 7 days. Data were analyzed using a paired t-test. Results: The average hemoglobin level increased significantly from 10.513 g/dl before the intervention to 11.357 g/dl afterward. The paired t-test results showed a p-value of 0.000, which proves a significant effect of giving avocado juice on increasing hemoglobin levels. Conclusion: The administration of avocado juice has a significant effect on increasing hemoglobin levels in anemic third-trimester pregnant women. Avocado juice can be an effective nutritional intervention alternative.